Responsibilities of Officials Making Land Deeds (PPAT) for Deeds of Sale and Purchase of Land That Give rise to Disputes - Resmi, Puji; Laksana, Andri Winjaya (TABELLIUS: Journal of Law, 2025)
The high strategic value of land makes it prone to disputes, so Land Deed Officials (PPAT) are required to understand land law in depth so that the deeds they make are legally valid and avoid legal conflicts due to misuse of transfer of rights. This study aims to analyze the importance of understanding land law for Land Deed Officials (PPAT) in ensuring the validity of land transfer deeds and preventing disputes due to misuse of land transactions. The type of research used is doctrinal research with a legislative and theoretical approach. Secondary data consists of primary, secondary, and tertiary legal materials. The data analysis method used is perspective analysis, which involves systematically compiling the data and then analyzing it descriptively and qualitatively to gain clarity on the research problem. The research results state that Land Deed Officials (PPAT) play a crucial role in ensuring the validity of land transactions through the preparation of authentic deeds, document verification, and registration with the National Land Agency, and are obligated to reject the issuance of deeds if there are disputes, incomplete documents, or indications of legal violations. Land disputes caused by duplicate certificates, unclear boundaries, illegal transactions, and slow settlement processes can be prevented by PPATs through proper procedures, and violations by PPATs can result in legal sanctions. Dispute resolution can be carried out non-penally through mediation and deliberation, or penally through the courts, in order to achieve legal certainty and fair protection for all parties.